Staff edutainment on a corporate intranetlessons learned - Vlad Ionesco (Association for Learning Technology, 1999)
The educational level required of a successful member of today's society and working environments is becoming higher and higher. National and commercial education systems are struggling, as increasing numbers of people must be trained within harsh budget constraints. In this context, internet technology has emerged as a new tool in the field of education and training, and the number of applications of this technology is increasing steadily. In order to assess its full potential, it is important to study cases in both educational and business settings.